Avaliação das características dos programas de prevenção ao uso de álcool e outras drogas implantados nas escolas brasileiras - Santos Neto, Miguel Teixeira dos [UNIFESP] (2016)
Objective: This study aimed to characterise alcohol and drug prevention programs employed by Brazilian public and private schools at the elementary and middle school levels. Methods: This is a qualitative study based on forty-one in-depth interviews conducted with directors and coordinators of Brazilian schools. Respondents were selected using a subsample of a national epidemiological survey aimed at assessing the presence of prevention programs in schools from five different regions. Interviews were conducted through Skype software, audio-recorded and transcribed, using a semi-structured script. In order to analyse data, NVivo software was used and interpretation of the collected material was subjected to further content analysis via Bardin’s theoretical framework. Results: We identified two categories of actions to prevent the use of alcohol and other drugs in schools: schools that had proper prevention programs and schools that performed specific prevention activities. Twenty-nine schools (or 71% of the total) who used prevention programs in their units were identified, while others made use of preventive activities. The program most frequently implemented in the investigated schools was the Educational Program of Resistance to Drugs (Proerd), which was applied in 54% (n = 22) of the schools. Other prevention programs included Nepre, Agrinho, Projeto Diretor de Turma (Class Principal), Protagonismo Juvenil (Youth Participation), Dignidade (Dignity): a Daily Conquest and of the Municipal Health Secretary of Rio de Janeiro (SMS). In 20 schools, prevention activities were combined with prevention programs and 12 schools offered only prevention acitvities. Prevention activities were less prevalent than programs, appearing in twelve schools, and were combined with programs in twenty of them. Such preventive activities included lectures, classes, seminars, recreational activities and visits to rehabilitation facilities. The most mentioned psychotropic drugs in the programs and activities were crack cocaine and marijuana. In the interviews, a general lack of information on ways to evaluate programs was noted. In addition, the applied programs do not show evidence of being effective and do not rely on good preventative practices. Conclusions: It was demonstrated that in Brazil, prevention programs are confused with preventative activities. The programs analysed do not follow good practices regarding alcohol and drug prevention and are not based on scientific evidence. The results of this study can help point out the need for national public policy development in order to encourage the implementation of evidence-based programs in school curriculums, thus avoiding potential iatrogenic effects from school-based alcohol and drug prevention efforts.